The Constitution is seventeen years old (Journal of Parents and Teachers, 1995)
The Constitution establishes the unity of the Spanish nation, recognizing the diversity of nationalities and regions. It guarantees rights and promotes solidarity among all Spaniards. It highlights the importance of a progressive Constitution that reaches its legal age of majority.
Keywords: unity; diversity; rights; Constitution